THE USE OF MONOLINGUAL DICTIONARY FOR VOCABULARY MASTERY OF TECHNICAL WORDS IN TEACHING READING COMPREHENSION OF FACTUAL REPORT TEXT TO THE ELEVENTH GRADERS IN SMA WAHID HASYIM 2 TAMAN SIDOARJO (RETAIN, 2015)
Abstrak Membaca secara comprehensif adalah proses yang sekaligus mengutip dan menafsirkan arti melalui interkasi dan melibatkan diri langsung dengan bahasa yang tertulis. Menafsirkan arti dari kosakata adalah penting sebagai aktivitas untuk memahami isi dari sebuah teks di dalam aktivitas membaca. Kamus satu bahasa adalah salah satu alat yang menampilkan kata-kata dalam berbagai definisi, simbol, dan informasi morphology yang memebantu siswa dalam memahami kata-kata teknis dan memperkaya vocabulary mereka dalam pengajaran membaca secara komprehensif dari teks faktual report. Penelitian ini menggambarkan penggunaan kamus satu bahasa untuk menguasai kosakata teknis dalam pengajaran membaca secara komprehensif dari teks faktual report untuk kelas 11 di SMA Wachid Hasyim 2 Tama, Sidoarjo. Kamus satu bahasa memberipembaca rincian yang lebih banyak tentang kata dan informasi yang lebih banyak seperti penggunaan ungkapan, kata yang sama dan kata tambahan (Laufer and Melamed, 1994:565). Penelitian ini menggunakan penelitian kualitatif. Mengumpulkan data dari kegiatan memebaca, peneliti merekam dan menulis penjelasan dari kegiatan siswa memebaca teks report dengan menggunakan kamus satu bahasa. Data ini diambil dari hasil observasi dengan mengisi field note, hasil dari wawancara, dan hasil dari pekerjaan siswa. Hasil dari penelitian ini menunjukkan bahwa guru lebih menyuruh siswanya untuk menggunakan kamus satu bahasa yang akan membantu mereka memeperkaya pengetahuan kosakata mereka, khususnya kosakata teknis. Kesimpulannya adalah siswa-siswa merasa terbantu dengan menggunakan kamus satu bahasa dalam memahami kosakata teknis yang selalu muncul dalam teks report and itu membuat mereka mengerti definisi jelas tentang kosakata teknis dalam bahasa inggris. Kata kunci : Membaca komprehensif, Kosakata teknis, teks faktual report, Kamus satu bahasa Abstract Reading comprehension is the process of simultaneously extracting and constructing meaning through interaction and involvement with written language. Constructing the meaning of vocabulary is important as an activity to understand the content of the text in reading activity. Monolingual dictionary is one of the tools that display many definitions of the words, symbols and other morphological information that can help the students in understanding technical words and enriching their vocabularies in teaching and learning process of reading comprehension of factual report texts. This research was to describe the use of monolingual dictionary for vocabulary mastery of technical words in teaching reading comprehension of a factual report text to the eleventh graders in SMA Wachid Hasyim 2 Taman, Sidoarjo. Monolingual dictionary gives the readers further details about the words and more information such as idiomatic usage and common collocations and connotations (Laufer and Melamed, 1994:565). This is a descriptive qualitative research. To collect the data of reading activity, the researcher recorded and transcribed the students’ reading report text completed by using monolingual dictionary. The data were obtained from the result of observation noted by using field notes, the result of interview, and the result of students’ works. The result revealed that the teacher prefers their students to use monolingual dictionary that can help the students enrich their vocabulary knowledge, especially vocabulary of technical words. In conclusion, the students feel assisted by using monolingual dictionary in understanding technical words that always appear in report text and it makes them understand the brief English definitions of technical words. Keywords: Reading comprehension, Technical words, Factual report text, Monolingual dictionary